Modelling the aerodynamics of propulsive system integration at cruise and high-lift conditions - Sibilli, Thierry (Cranfield University, 2012)
Due to a trend towards Ultra High Bypass Ratio engines the corresponding engine/airframe interference is becoming a key aspect in aircraft design. The present economic situation increases the pressure on commercial aviation companies to reduce the Direct Operating Cost, and the environmental situation requires a new generation of aircraft with a lower environmental impact. Therefore detailed aerodynamic investigations are required to evaluate the real benefits of new technologies. The presented research activity is part of a long-term project with the main objective of generating a reliable and accurate tool to predict the performance of an aircraft over the whole flight domain. In particular the aim of this research was to perform advanced CFD in order to establish a tool able to evaluate engine installation effects for different configurations and attitudes. The developed tool can be provided with correlations of the Net Propulsive Force (NPF), the force exerted by the power-plant to the aircraft, as a function of position. This can be done in principle at cruise, hold, climb, descent, take-off and landing, to model the different integration effects at different phases. Due to the complexity of the problem it was only possible at an initial stage to determine these correlations at cruise condition. Two parametric test cases were evaluated, showing that the engine horizontal positioning can influence the mission fuel burn by up to 6.4%. According to the extensive literature review that has been done, this study can be regarded as the first open literature engine position-NPF parametric study using CFD. Even though no correlations were extracted for other conditions; a deployed high-lift wing configuration was also studied in detail, defining the main aerodynamics effects of the engine integration at high angle of attack. A topological study of the high-lift installation vortices is presented in this work and it can be considered the first in the open literature. It should be pointed out that extensive research is currently underway to correctly evaluate the high-lift aerodynamic using CFD. The Propulsive System Integration (PSI) in high-lift conditions is adding flow features to an already demanding problem, making it a real challenge for the numerical methods. Nevertheless the additional effects of a nacelle chine on the maximum lift were also evaluated. The main outcomes of this PhD research were: a coupled performance modelling tool able to handle the effects of engine-airframe integration as a function of geometry and attitude, and a topological study of the high-lift installation vortices. During the course of the work, this research was successfully suggested as an extra activity for the European NEWAC project (New Aero Engine Core Concepts), and resulted in a new deliverable for that project.
Keywords: Engine-Airframe Interaction; Net Propulsive Force; High-Lift CFD; High-lift Installation Vortex; Nacelle chine; Drag Extraction